Hubungan Interaksi Sosial dengan Kecerdasan Emosional Siswa di SMPN 1 Sungai Geringging - Mailinda, Vany Enika; Zikra, Zikra (ANWARUL, 2023)
This research is motivated by the phenomenon of students who experience social interaction problems, students feel embarrassed when they start interacting with their friends where they feel they will not be accepted in their social environment, and students who have difficulty in social interaction in the school environment often act indifferent when their friends are speak. This research uses a quantitative approach with a descriptive correlational research type. The population of this study was 421 students and the sample was 205 students using the stratified random sampling formula. Data were collected using a Likert scale model questionnaire and validity tests were carried out with valid items totaling 36 social interaction questionnaire items and 29 emotional intelligence questionnaire items. Meanwhile, the reliability test on the social interaction questionnaire was 0.919 and the emotional intelligence questionnaire was 0.910. Data analysis uses descriptive statistics using the person product moment correlation formula. The results of the research show that (1) The social interaction of students at SMPN 1 Sungai Geringging is at varying levels, most of it is in the medium category with a percentage of 56.10% (2) The emotional intelligence of students is at varying levels, most of it is in the medium category with percentage 54.63% (3) there is a positive and significant relationship between Social Interaction and the Emotional Intelligence of students at SMPN 1 Sungai Geringging with a calculated r value of 0.423 with an aggressiveness level of 0.000). Therefore, guidance and counseling services are needed to improve students' social interaction and emotional intelligence through information services, content mastery services and group guidance services.